Authors-at-law: the jurisprudence of investigation in the detective fiction of Dashiell Hammett and William Faulkner - Shahinyan, Diana Louis (2014)
The configuration of law and literature has produced a rich field of studies in which, inter alia, critics have looked to literary texts in order to gain access to narratives pertaining to justice that do not need to conform to the substantive and procedural norms of the law. The private detective, who traditionally operates outside of and is unrestricted by the law and its exigencies, is an apt personification of the nexus of law and literature: the private detective is commissioned to find clues and weave narratives around a central crime, to understand and subsequently narrativize a criminal landscape. The hardboiled, modern detective of the early twentieth century is a particularly enticing figure: he detects through epistemological uncertainty, and, unlike the formal judicial function of the law, is able to evade conclusiveness and instead appreciate the paradoxical, the local, the ontologically perverse, the emotional, the whimsical, the meaningless and the relative – and the possibility of the formless and arbitrary simultaneity of these conditions. This thesis will examine the detective stories and novels of Dashiell Hammett and William Faulkner, and argue that both authors, in employing the figure of the private detective, attempt to bring into question and resolve perceived injustices of their time. What explicitly links Hammett and Faulkner is that they present detective-heroes who conform to a classic American jurisprudential model which locates justice not in a specific destination but rather in the activity of interpretation, oratory, and the pursuit of meaning. Moreover, in tracing the evolution of Hammett’s detectives – from the Continental Op, to Sam Spade, through to Nick and Nora Charles – alongside the evolution of Faulkner’s Gavin Stevens, this thesis charts the struggle of the private detectives to understand the world around them, even with the extra-legal and extra-systemic freedom the genre affords them – perhaps because of it. Ultimately, both Hammett and Faulkner wound up at the same place, with the genre suffering a defeat: the detectives, overcome by cynicism, retire to stasis and abandon their pursuit, effectively deferring to the law to make sense of the senselessness against which they failed to forge meaning and narrative. For both Hammett and Faulkner, it is not that the law wins – it is still as problematic as ever. Rather, as intimated in Faulkner’s Sanctuary, the law triumphs because – in its tenacious search not for truth but for resolution, and not for meaning but simply for consistency and uniformity – it is “in lieu of anything better.